Noun Phrase Conjunction in Akan: the grammaticalization Path - Amfo, N.A.A. (Pragmatics 20(1): 27-41, 2010)
Noun phrase conjunction in Akan (Niger-Congo, Kwa) is performed by placing a connective between two noun phrases, but there is some variation in the forms used in the major dialects. In the Twi dialects the connective is ne, but Fante speakers may use nye or na depending on whether a comitative or a coordinative interpretation is intended. This paper focuses on the historical origins of the noun phrase connective n(y)e in Akan. It suggests that Akan patterns with other sub-saharan African languages such as Ewe, Ga, Yoruba and Hausa, which have noun phrase connectives originating from comitative verbs. This suggestion is based on the morpho-semantics of these connectives. In addition, the paper demonstrates that the origin of the connective n(y)e could be further traced to an equative copula in the language. This conclusion is based on syntactic and semantic evidence available in the language and strengthened by the cross-linguistic tendency for copula verbs to develop into noun phrase connectives in a number of unrelated languages.
Keywords: Akan; Comitative; Conjunction; Coordinative; Grammaticalization